2018
DOI: 10.1055/a-0611-4825
|View full text |Cite
|
Sign up to set email alerts
|

White opaque substance visualized by magnifying narrow-band imaging is associated with intragastric acid conditions

Abstract: Background and study aims  The presence of white opaque substance (WOS) is an endoscopic marker of intestinal metaplasia. Considering that the nature of WOS is absorbed lipid droplets, lipase plays an important role in the lipid absorption process and is inactivated at strong acidity. WOS may only be present in a hypochlorhydria state following Helicobacter pylori infection, and, thus, may not be highly sensitive marker, especially in H. pylori- eradicated patients. We investigated the relationship between WOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…A cross-sectional study including a total of more than 76 000 patients undertaken by Eisdorfer compared to 62.6% in the lower quintile (OR: 1.22; 95% CI: 1.11-1.35, P < .01), that is, a small but significant difference. The diagnostic odds ratios (OR) for 13 C-UBT, 14 C-UBT, serology, and SAT were 153, 105, 47, and 45, respectively (a higher diagnostic OR being indicative of better test performance). The authors therefore hope that this may contribute to a wider dissemination of this test in the country; its availability is currently restricted to large cities and university centers.…”
Section: Urea Breath Test (Ubt)mentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study including a total of more than 76 000 patients undertaken by Eisdorfer compared to 62.6% in the lower quintile (OR: 1.22; 95% CI: 1.11-1.35, P < .01), that is, a small but significant difference. The diagnostic odds ratios (OR) for 13 C-UBT, 14 C-UBT, serology, and SAT were 153, 105, 47, and 45, respectively (a higher diagnostic OR being indicative of better test performance). The authors therefore hope that this may contribute to a wider dissemination of this test in the country; its availability is currently restricted to large cities and university centers.…”
Section: Urea Breath Test (Ubt)mentioning
confidence: 99%
“…Using data from 99 studies in an indirect test comparison, statistical evidence of a difference in diagnostic accuracy between these tests could be confirmed. The diagnostic odds ratios (OR) for 13 C-UBT, 14 C-UBT, serology, and SAT were 153, 105, 47, and 45, respectively (a higher diagnostic OR being indicative of better test performance). The sensitivity estimated at a specificity of 90% (median from studies across the four tests) was 94% for the 13 C-UBT, 92% for the 14 C-UBT, 84% for serology, and 83% for SAT.…”
Section: Urea Breath Test (Ubt)mentioning
confidence: 99%
“…Studies of Helicobacter pylori infection-associated intestinal metaplasia of the stomach using lipid staining and light microscopy or electron microscopy showed that the epithelium in intestinal metaplasia has ability to absorb lipid droplets 6 7 . We have more recently clarified clinical significance of WOS which signifies “absorbed lipid droplets” in intestinal metaplasia and its limitations from the perspective of intragastric acid conditions 8 9 . Interestingly, presence of WOS in intestinal metaplasia was closely associated with a state of hypochlorhydria following H. pylori infection, and WOS was not observed in intestinal metaplasia following acid recovery after H. pylori eradication 8 9 .…”
Section: Introductionmentioning
confidence: 99%
“…We have more recently clarified clinical significance of WOS which signifies “absorbed lipid droplets” in intestinal metaplasia and its limitations from the perspective of intragastric acid conditions 8 9 . Interestingly, presence of WOS in intestinal metaplasia was closely associated with a state of hypochlorhydria following H. pylori infection, and WOS was not observed in intestinal metaplasia following acid recovery after H. pylori eradication 8 9 . This is because lipase, which plays a crucial role in lipid digestion and absorption, is inactivated in strong acidity 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation